Proses Sebagai Bagian Terpenting dalam Dunia Pendidikan - asef umar Fakhruddin (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
An effort to cultivate process spirit to student has to be done patiently.Â  That process will make them remember that success is an accumulation of ability to solve the problem. Big success is an accumulation of little successes. Long-term objective achieved with midterm and short-term effort. Every success full people have reached his point with process full of strategy, struggle, patience and perseverance. Participative education enriched with process will teach student to think critical and open mind.